2023
DOI: 10.1002/fsn3.3644
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the multitargeted antidiabetic potential of three pomegranate peel‐specific metabolites: An in silico and pharmacokinetics study

Hina Gull,
Aqsa Ikram,
Anees Ahmed Khalil
et al.

Abstract: Diabetes is a chronic metabolic disorder that occurs due to impaired secretion of insulin, insulin resistance, or both. Recent studies show that the antidiabetic drugs used to control hyperglycemic levels are associated with undesirable adverse effects. Therefore, developing a safe and effective medicine with antidiabetic potential is needed. In this context, in silico studies are considered a rapid, effectual, and cost‐effective method in drug discovery procedures. It is evident from the literature that plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Phenolic compounds have been shown to control glycemia, which is attributed to the inhibition of salivary and pancreatic enzymes during sugar digestion. 66 Specifically, some phenolic molecules that are mainly present in the obtained extracts have been reported as potential antidiabetic agents, such as didymin and punicalgin, 67,68 69 Photoperiod effects on blood glucose levels were also observed in F344 rats exposed to different photoperiods and consuming the enriched-phenolic grape seed extract GSPE for 9 weeks, although and unlike in the current study, GSPE increased its concentration in the L6 and L18 photoperiods compared to their respective control animals and treated and untreated L12-exposed animals. 21 In healthy animals, insulin is released by the pancreatic islets after carbohydrate meals to remove glucose from the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds have been shown to control glycemia, which is attributed to the inhibition of salivary and pancreatic enzymes during sugar digestion. 66 Specifically, some phenolic molecules that are mainly present in the obtained extracts have been reported as potential antidiabetic agents, such as didymin and punicalgin, 67,68 69 Photoperiod effects on blood glucose levels were also observed in F344 rats exposed to different photoperiods and consuming the enriched-phenolic grape seed extract GSPE for 9 weeks, although and unlike in the current study, GSPE increased its concentration in the L6 and L18 photoperiods compared to their respective control animals and treated and untreated L12-exposed animals. 21 In healthy animals, insulin is released by the pancreatic islets after carbohydrate meals to remove glucose from the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds have been shown to control glycemia, which is attributed to the inhibition of salivary and pancreatic enzymes during sugar digestion . Specifically, some phenolic molecules that are mainly present in the obtained extracts have been reported as potential antidiabetic agents, such as didymin and punicalgin, , which are mainly present in orange and pomegranate extracts, respectively. In addition, another study showed that pomegranate and grape extracts could modulate carbohydrate digestive enzyme activity, including in vitro inhibition of α-amylase and α-glucosidase .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the existence of several therapeutic agents for the treatment of DM, adverse effects have been observed, such as gastrointestinal disturbances, nausea, vomiting, hypoglycemia, and weight gain, and also the lack of effectiveness in some cases [97,98]. Nonetheless, the natural progression of DM calls for multiple drugs in addition to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The peel of the pomegranate contains a variety of bioactive substances, including quercetin, catechin, antioxidants, minerals, and vitamins, as well as several potential health benefits (Pirzadeh et al., 2020 ). These substances are essential for preserving health and provide defense against a number of crippling conditions like cardiovascular diseases (CVD, diabetes, and specific types of cancer (Gull et al., 2023 ). The numerous uses of pomegranate peel in the fields of food biopreservation, the development of nutraceutical products, and the production of value‐added items are also explored through current research.…”
Section: Introductionmentioning
confidence: 99%